2000
DOI: 10.1002/(sici)1099-0984(200003/04)14:2<157::aid-per366>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Personality and the use of intuition: individual differences in strategy and performance on an implicit learning task

Abstract: There is a divergence of opinion regarding the existence of individual dierences in the use of intuition, ranging from intuition being the preserve of a creative minority to intuition as a basic cognitive process that is equally accessible to all. The existence and nature of individual dierences in the use of intuition were explored by studying relationships between the sensing±intuition scale of the Myers±Briggs Type Indicator and strategy and performance on an implicit learning task. Results indicated dieren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 17 publications
(27 reference statements)
3
23
1
Order By: Relevance
“…Numerous studies have found only a modest correlation between implicit learning performance and individual differences in cognitive ability (Gebauer & Mackintosh, 2007Kaufman et al, 2009;Reber, Walkenfeld, & Hernstadt, 1991). However, as mentioned, some evidence has shown a correlation between an intuitive cognitive style and implicit learning performance (Woolhouse & Bayne, 2000). Recent work by Kaufman et al (2009) found that SRT significantly correlated with openness to experience and the intuition facet of the Myers Briggs (MBTI).…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 58%
See 1 more Smart Citation
“…Numerous studies have found only a modest correlation between implicit learning performance and individual differences in cognitive ability (Gebauer & Mackintosh, 2007Kaufman et al, 2009;Reber, Walkenfeld, & Hernstadt, 1991). However, as mentioned, some evidence has shown a correlation between an intuitive cognitive style and implicit learning performance (Woolhouse & Bayne, 2000). Recent work by Kaufman et al (2009) found that SRT significantly correlated with openness to experience and the intuition facet of the Myers Briggs (MBTI).…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 58%
“…Preferences for the experiential mode were found to correlate with heuristic responding in a laboratory gambling task (Pacini & Epstein). Similarly, preference for intuition (as measured by the Myers Briggs Intuitive/Sensate subscale) was found to correlate with implicit learning (Woolhouse & Bayne, 2000). Our predictions for the effect of cognitive style on implicit learning follow from dual process theory.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 87%
“…Applying a different experimental procedure, Woolhouse and Bayne (2000) found a relationship between cognitive intuitive style, as measured by MBTI, and performance on a HCD task.…”
Section: Implicit Learning and Individual Differencescontrasting
confidence: 74%
“…However, a number of recent studies have challenged this view by showing evidence of individual differences in implicit learning ranging from aspects of psychometric intelligence to personality factors (Norman, Price, & Duff, 2006;Woolhouse & Bayne, 2000). More specifically, Kaufman et al (2010) found that implicit learning as measured by an SRT task was related to a number of individual difference variables, including verbal analogical reasoning and processing speed aspects of psychometric intelligence, performance on two foreign language exams, as well as intuition, openness to experience and impulsivity.…”
Section: Implicit Learning and Individual Differencesmentioning
confidence: 93%
“…Further, although the MBTI has been widely applied, it was developed by amateurs and it, too, had no basis in experimental work (Carroll, 2003). Woolhouse and Bayne (2000) found that there were no significant relationships between use of intuition and gender. Boucouvalas (1997) suggests that the issue of gender differences in use of intuition is semantic, with men preferring to use terms like ''hunch'' and ''gut feeling'' rather than intuition.…”
Section: Individual Differencesmentioning
confidence: 99%